Days Of Hospitalization Due To Childhood Malnutrition In The Years 2011 Through 2022 In Brazil - Epidemiological Review - de Miranda, Dener Hayek; Martins, Camila Nunes; Lopes, Gustavo Vieira; da Paixão, Isabella Vicente; Rezende, Lucas Alves Oliveira; de Castro, Lucas Brito; Chater, Michel Sebba; Bertoldi, Paulo Fernando Evangelista; Carneiro, Sara Baiocchi Ferro; Santana, Vinícius Costa (Seven Editora, 2023)
This epidemiological review aims to show that malnutrition, with emphasis on childhood malnutrition, is a global issue that has numerous consequences for the child population that presents this condition, seeing the complexity and dimension that this clinical picture has, this study highlights the number of days of hospitalization that patients under one year to nineteen years, i.e., children and adolescents, stay due to worsening malnutrition. Thus, due to the facts indicated, this work described the five Brazilian regions and the number of days of hospitalization that each one had, showing that the region with the highest number of days of hospitalization was the Northeast region and the one with the lowest number was the North region. DOI: https://doi.org/10.56238/colleinternhealthscienv1-115